Living Together with LGBT: A Discussion from the Sharia Perspective - Mohd Azhar Abdullah; Nur Azwani Mansor; Abdul Azib Hussain; Muhammad Lukman Ibrahim; Khairulnazrin Nasir (Rabbanica: Journal of Revealed Knowledge)
Living together with individuals who identify as lesbian, gay, bisexual, or transgender (LGBT) demands significant consideration, particularly when they cohabit as partners. The promotion of LGBT ideologies alongside social media advancements and human rights advocacy has led to an increasing prevalence of same-sex relationships. Some youth in Malaysia have embraced LGBT as a modern, liberated lifestyle. They engage in intimate relationships, including cohabitation between gay or lesbian partners, as though they were married couples, disregarding religious boundaries and moral values. The public often remains indifferent to such cohabitation due to the assumption that it involves individuals of the same gender. While there is extensive research on gender identity disorders among LGBT individuals, which covers aspects such as contributing factors, influences, psychology, and rehabilitation, there is limited discourse from a Sharia perspective on the legality and implications of cohabitation. This study uses a qualitative method to look at the basics of Islamic law in this area. Specifically, it looks at the possible dangers of slander (fitnah) and how the principle of sadd zara’i (blocking the means) can be used to stop immoral acts. The strength of this research is supported by evidence that unrestricted social interactions can lead to negative psychological impacts and deviant behaviours. The primary objective of this study is to provide an in-depth understanding of the Sharia prohibitions against same-sex intimate relationships. Additionally, the study proposes Sharia-compliant guidelines for situations where individuals may cohabit with LGBT persons.